The cost of peace: assessing the domestic impacts of Nigeria's military deployments to ECOMOG operations - Afaha, Philip (2014)
A new wave of thinking is evolving in diplomacy: that of deploying military resources for peace instead of war. This new method which gained currency immediately after the World War II and has come to shape international relations in the beginning of the 21st century is constantly bedeviled by far reaching socio-economic implications due to the often haphazard and disarticulated approach of such engagements. Although Nigeria stands tall as a vanguard of peacekeeping around the world, the collateral impacts of these overtures on her domestic affairs has been daunting. From 1960 when she first sent her troops to quell the crisis in the Congo, the country has participated in more than 30 peace missions around the globe, some of which she actually initiated. Nigeria`s spearheading of ECOMOG operations was not without some far reaching impacts on the home front. Her experiences in spearheading the ECOMOG missions in Liberia and Sierra Leone came with not only tales of war but other extra-military impacts suffered by the country during and after those operations. This paper attempts to interrogate such domestic fall-outs and argues for a sufficient articulation of such exercises to mitigate longterm impacts.